Ethanolic flower extract from Laccopetalum giganteum (pacra-pacra) increases fertility in rats - Arroyo, Jorge (2007)
Objective: To determine whether oral administration of the ethanolic flower extract from Laccopetalum giganteum (pacra-pacra) increases fertility in normal rats. Design: Experimental study. Setting: Faculty of Medicine and Faculty of Pharmacy and Biochemistry, Universidad Nacional Mayor de San Marcos. Biologic material: Rats. Interventions: Forty-eight rats were randomly distributed into 2 groups of 24 rats each. The first control group received solución salina fisiológica (SSF) 5 mL/kg and the second group 300 mg/kg of the extract, orally, for 15 days. Each group had 6 female rats and 6 male rats living together and 6 female rats and 6 male rats lived separate. The animals living together were sacrificed in order to observe the fetuses in the uterus. The animals that lived separate had blood samples taken in order to determine testosterone levels in male rats and LH, FSH, estrogen and progesterone levels in female rats using electro chemiluminescence. At the same time, liver function tests, urea and creatinine tests were done. Main outcome measures: Pregnancy, FSH, LH, estrogens and progesterone in female rats; testosterone in male rats. Results: Flavonoids, tannins and phenolic compounds were found in higher quantities in the ethanolic extract. All female rats receiving the plant extract and living together with the male rats got pregnant and the ones that lived separate had increased levels of FSH. Male rats had increased levels of testosterone as compared to the control group. Liver function tests, urea and creatinine were within acceptable limits. Conclusions: The ethanolic flower extract from Laccopetalum giganteum (pacra-pacra) increased fertility in normal rats.